Cancellation of A Defective Deed of Grant By Law Because The Object Granted Was Not Made Before A Notary/PPAT - Jessica Sim; Sri Laksmi Anindita (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
This research analyzes the cancellation of a gift deed which is legally flawed because the object being gifted was not made before a Notary/PPAT in the case study of the Kupang District Court decision number 298/PDT.G/2021/PN KPG. One way for someone to legally transfer their rights is by gift by making a gift deed before a Notary/PPAT. If the object being donated is land, then the grant transfer process must be carried out through PPAT. In this case, the Notary/PPAT concerned did not read and sign the deed which should have been carried out in the presence of the presenters and witnesses at the same time so that the deed did not become legally defective. This research uses normative juridical research methods that are analytical descriptive with secondary data. The legal materials used in this research are divided into three, namely primary legal sources consisting of civil law books, secondary legal sources consisting of law journals and tertiary legal sources consisting of legal dictionaries. The data analysis method used in this research is qualitative, namely the data is arranged in the form of a narrative. The deed of gift made by a Notary/PPAT is legally flawed which causes the deed to be null and void. The Notary/PPAT's actions can be held accountable administratively and civilly with sanctions in the form of a written warning and compensation.